Utilization of Native Chicken Egg Shells as Abrasive Ingredients in Toothpaste - A Asmawati S; Jumasni Adnan; Hery Wajarwanto (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2023)
Native chicken eggs are one of the eggs that are often consumed by the community. Grafting native chicken eggs has a lot of mineral content that is good for dental health, namely calcium. In toothpaste calcium has properties as an abrasive which can reduce plaque formation on teeth. The purpose of this study was to determine the abrasive effect of toothpaste preparations from native chicken egg shells and to determine the stability of toothpaste preparations with active ingredients from native chicken egg shells. The research method carried out is laboratory experimental on the formulation of toothpaste preparations from native chicken egg shells. Toothpaste preparations are made with a variant of the concentration of native chicken egg shell waste powder of 30%, 35%, 40% then an evaluation of the quality of the preparation before and after storage is carried out to determine the stability of a preparation. Based on the results of this study obtained, toothpaste preparations with a concentration of egg shell powder of 35% are effective in reducing plaque on artificial teeth. Based on the evaluation requirements of SNI No. 12-3524-1995 including organoleptic tests, pH, dispersality, foam formation and homogeneity obtained all formulas are qualified.